A SEMANTIC ANALYSIS OF CONNOTATIVE MEANING IN DONALD TRUMP’S SPEECH AT THE BOARD OF PEACE - Opirman Waruwu; Gabriel Mau Mali (Research on English Language Education, 2025)
This study aims to analyze the connotative meanings found in the speech delivered by Donald Trump at the Board of Peace meeting. The objective of this research is to identify and explain words and phrases that contain connotative meanings in the speech. This study uses a qualitative research design because it focuses on interpreting meanings embedded in language rather than numerical data. The data of this research were taken from the transcript of Donald Trump’s speech obtained from a video published on the YouTube channel of Kompas TV entitled “Pidato Trump di Board of Peace: Gaza, Perdamaian, dan Kepemimpinan Global” with the hashtag #boardofpeace. The data were collected using the documentation method by identifying words and phrases that potentially contain connotative meanings. The data were analyzed using the theory of connotative meaning proposed by Geoffrey Leech. The findings of this research show that there are 27 expressions containing connotative meanings in the speech. These expressions are used to emphasize important messages, strengthen persuasive communication, and highlight themes such as leadership, diplomacy, cooperation, and peace. The study concludes that connotative meaning plays an important role in political speeches because it helps convey deeper messages and influence audience perception.